Factors influencing agent’s retention in insurance industry: survey of ING Public Takaful Ehsan / Nur Izzati Mohd Isa and Noor Khamisah Lailah Abdul Wahed - Mohd Isa, Nur Izzati; Abdul Wahed, Noor Khamisah Lailah (Faculty of Business and Management, 2013)
Recently, life insurance industry has been suffering high rate of retention of the agents’ therefore this research has been conducted to study the factors influencing agents’ retention in insurance industry in Malaysia, which focused on ING PUBLIC Takaful Ehsan Berhad. As the roles of insurance agent itself seriously important to insurance companies, therefore, they must retain their agents as much as possible. This research is aims to explore the relationship between training and development, working condition and remuneration with the retention of agents mainly in ING PUBLIC Takaful Ehsan Berhad. To examine this research, there are three factors that influencing retention of agents which are training and development, working condition and remuneration. The purpose or objective of this research is to identify the relationship among these factors that can influence retention of agents. The respondents are from the agents of ING PUBLIC Takaful Ehsan. 100 questionnaires had been distributed among them. The finding shows that training and development is the most influence factors that influencing agents’ retention, followed by working condition. For the remuneration, it shows a weak relationship with agents’ retention. So that, insurance company must make improvement on the factors that influencing their agents’ retention especially the training and development program.